PENGGUNAAN APLIKASI ZAHIR PADA PERUSAHAAN DAGANG UNTUK MEMBUAT LAPORAN KEUANGAN - Faddillah, Umi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
Accounting information systems ranging from the balance at beginning of period, journaling, posting ledger, trial balance at end of period, the adjusting entry to preparing the reports at end of period experience recording errors, lack of accurate financial statements that were made and the delay in the search data of financial accounting. Application of Accounting Information Systems to collect data of financial transactions manually and searching for literature on financial accounting information systems to support theories relating to the processing of financial data using application Zahir. Utilization Zahir applications to process financial data in accounting information system is a data recording error solutions in accounting, financial reporting delays and the accuracy of the search data of financial accounting.Keyword : Accounting information systems, financial data, zahir